Towards a better recording of microtubule cytoskeletal spatial organization and dynamics in plant cells. Issue 4 (26th November 2018) - Liu, Weiwei; Wang, Chaofeng; Wang, Guangda; Ma, Yinping; Tian, Juan; Yu, Yanjun; Dong, Li; Kong, Zhaosheng
Summary: Numerous fluorescent marker lines are currently available to visualize microtubule (MT) architecture and dynamics in living plant cells, such as markers expressing p35S::GFP‐MBD or p35S::GFP‐TUB6 . However, these MT marker lines display obvious defects that affect plant growth or produce unstable fluorescent signals. Here, a series of new marker lines were developed, including the pTUB6::VisGreen‐TUB6‐ expressing line in which TUB6 is under the control of its endogenous regulatory elements and eGFP is replaced with VisGreen, a brighter fluorescent protein. Moreover, two different markers were combined into one expression vector and developed two dual‐marker lines. These marker lines produce bright, stable fluorescent signals in various tissues, and greatly shorten the screening process for generating dual‐marker lines. These new marker lines provide a novel resource for MT research. Abstract : We developed a series of new marker lines including dual‐marker lines for better observing spatial organization and dynamics of the microtubule in plant living cells. These marker lines produce bright, stable fluorescent signals in various tissues, and greatly shorten the screening process in generating dual‐marker lines.